Asymmetric synthesis of common aza-tricyclic core of various alkaloids. Issue 40 (30th September 2015) - Ding, Ming; Tong, Xiaogang; Li, Dashan; Liang, Kangjiang; Zhou, Ankun; Zuo, Zhili; Xia, Chengfeng
Graphical abstract: Abstract: The asymmetric synthesis of common aza-tricyclic core of different types of natural alkaloids had been accomplished from commercially available l -Cbz-tyrosine. This practical approach was capable of generating scale-up aza-tricyclic skeleton. Meanwhile, it will facilitate the manipulating functionalities on the aza-tricyclic framework further, for the purpose of target-oriented synthesis of a large number of different natural alkaloids containing this versatile aza-tricyclic structure.